Decreased expression of long non-coding RNA GAS5 promotes cell proliferation, migration and invasion, and indicates a poor prognosis in ovarian cancer - Li, Jie; Huang, He; Li, Yingguang; Li, Li; Hou, Wenhui; You, Zeshan (Oncology reports, 2016)
Long non-coding RNA growth arrest-specific 5 (GAS5) was reported to be aberrantly expressed in various types of cancers. However, the role of GAS5 in the evolution and progression of ovarian cancer remains elusive. In the present study, we aimed to investigate the cellular function and clinical significance of GAS5 in ovarian cancer. GAS5 expression levels in 63 ovarian cancer tissues were detected by quantitative real-time PCR. Cell Counting Kit-8 (CCK-8) assay was performed to analyze the effect of GAS5 on cell proliferation. The effect of GAS5 on cell migration and invasion was detected using Transwell assay. Cell apoptosis was evaluated by flow cytometry and Hoechst staining. SKOV3 cells with stable expression of GAS5 were injected into nude mice to study the effect of GAS5 on tumorigenesis in vivo. Western blotting was used to determine the protein levels of GAS5 potential targets. The results showed that GAS5 was markedly decreased in tumor tissues and a lower expression of GAS5 was detected in tumors with larger size, deeper invasive depth and higher tumor stage. Patients with low GAS5 expression level had poorer disease-free (P<0.0001) and overall survival (P=0.0016) than those with high GAS5 expression. Moreover, overexpression of GAS5 was demonstrated to suppress ovarian cancer cell proliferation in vitro and in vivo. Finally, we found that GAS5 influenced ovarian cancer cell proliferation, partly via regulating cyclin D1, p21 and apoptosis protease activating factor 1 (APAF1) expression. Our findings suggest that lncRNA GAS5 may represent a novel indicator of poor prognosis in ovarian cancer and may be a potential therapeutic target for diagnosis and therapy.